Strategic management accounting: definitions and dimensions - Pires, Rui A.R. (2018)
The purposes of this paper are twofold: firstly it aims to discuss prior definitions of strategic management accounting (SMA) in order to understand the main purposes and the scope of SMA; secondly the management accountant’s participation in the strategic decision-making and SMA practices are discussed. The SMA literature review shows us that there is no consensus in the SMA definition. However, there is some common elements in the SMA definitions, such as: i) a development of management accounting with a strategic orientation; ii) an external orientation (outward-looking orientation); and, iii) an orientation for future (forward-looking orientation). In addition, SMA adopts both financial and non-financial measurement typologies and an orientation to internal resources and organizational capabilities (intellectual capital). There is also some consensus on the main purpose. SMA must cooperate and provide strategic information for the strategic management, marketing, and other managerial functions. The purpose is to create and achieve competitive advantages and enhance organizational performance. To accomplish this goal SMA considers two dimensions related with the management accountant’s participation in the strategic decisionmaking process and a set of SMA practices. Therefore, this paper contributes to a better understanding of the concept and scope of SMA and its two dimensions. In this sense, it assists practitioners and researchers to understand, adopt, use, and research the SMA.